Prognostic Value of N-Terminal Prohormone of Brain Natriuretic Peptide (NT-ProBNP) and Killip Score in Patients with Acute Decompensated Heart Failure (ADHF): A Sarawak Tertiary Centre Experience - Ling, H.S.; Chung, B.K.; Chua, P.F.; Fong, A.Y.Y. (Elsevier, Inc., 2019)
Mortality and readmission due to heart failure is contributing to increase healthcare burden. NT-proBNP is known for its role in diagnosis of heart failure. Higher Killip score was found to be associated with more inpatient death among ADHF patients in Sarawak General Hospital. There are limited data on usage of NT proBNP and Killip score to prognosticate post discharge clinical outcome.